2020
DOI: 10.1097/md.0000000000019520
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vonoprazan for initial and maintenance therapy in reflux esophagitis, nonerosive esophagitis, and proton pump inhibitor-resistant gastroesophageal reflux disease

Abstract: Proton pump inhibitors (PPIs) have been the first line treatment for gastroesophageal reflux disease (GERD). The aim of this study was to evaluate the efficacy of vonoprazan (VPZ), a potassium-competitive acid blocker for reflux esophagitis (RE), nonerosive reflux disease (NERD), and PPI-resistant GERD patients. An open-label, single-center, observational study in our hospital was performed from August 2016 to August 2017. All patients diagnosed with GERD were asked to self-report a questionnaire of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…These included studies which were published between 2015 and 2022. Seventy-four studies were conducted in Asia, 1015,1922,2428,3053,55…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These included studies which were published between 2015 and 2022. Seventy-four studies were conducted in Asia, 1015,1922,2428,3053,55…”
Section: Resultsmentioning
confidence: 99%
“…23,29,54 Thirty-four studies were RCTs, 1014,1923,3235,38,4244,46,52,54,55,57,60,61,63,72,74,77,80,83,85,86,89 24 cohort studies, 15,24,27,31,36,37,41,47,50,51,53,56,59,62,6467,71,75,79,81,84,87 and 19 single-arm studies. 25,26,28–30,39,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A final list of 12 studies was included in this systematic review, and the reasons for full-text exclusion are detailed in Table S3. Of the included studies, eight were prospective, 5,[11][12][13][14][15][16][17] and four were retrospective (Table S4). 6,[18][19][20] All studies except for three had included only standard-dose PPI-resistant GERD patients; two studies 13,18 included both standard-dose or double-standard dose PPI-resistant GERD, and one study 20 included only double-standard dose PPI-resistant GERD.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some patients remained symptom‐free for 4 weeks 159 . An open‐label, single‐center observational study showed that both initial and maintenance vonoprazan therapies significantly improved heartburn in patients with PPI‐resistant GERD 160 …”
Section: Introductionmentioning
confidence: 99%